Financial Performance Analysis of PT Indofood Sukses Makmur Tbk in Period 2021-2023 - Ajeng Intan Amalia; Haryono, Haryono (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The purpose of this study is to determine the benefits of financial ratio analysis and to assess the financial condition and performance of the company PT Indofood Sukses Makmur Tbk in the 2021-2023 period listed on the Indonesia Stock Exchange (IDX). This study uses a descriptive quantitative method by collecting, executing, and interpreting the data obtained to obtain a clear description of the object being studied based on the numbers and the data used is secondary data in the form of financial reports of PT Indofood Sukses Makmur Tbk for the 2021-2023 period obtained from the official website of the Indonesia Stock Exchange (IDX) www.idx.co.id Then analyzed using financial statement analysis consisting of Liquidity Ratio, Solvency Ratio, and Profitability Ratio. It can be concluded from the results of the calculations that have been carried out using the financial ratio analysis mentioned above that the Liquidity Ratio measured using CR and QR gets good results, while the Solvency Ratio measured using DAR and DER gets good results too and the Profitability Ratio measured using NPM, ROA and ROE gets quite good results.